Honduras : Selected Issues. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 1998)
This Selected Issues paper analyzes growth performance and constraints for Honduras' economy. The findings indicate that Honduras' low growth rates in real per capita GDP reflect the influence of a combination of factors. Policy- and efficiency-related variables, exogenous shocks, and political uncertainty seem to have had less of a negative influence on growth in Honduras than they have had on the comparator groups. Instead, low growth appears to be closely related to the low productivity of labor and capital, and the poor composition of investment and inadequate physical infrastructure.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet